PENGARUH KINERJA KEUANGAN DAN KEBIJAKAN DIVIDEN TERHADAP REAKSI INVESTOR PADA PERUSAHAAN OTOMOTIF - Ayuni, Alfiyanti Devie Nor; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze the influence of financial performance and dividend policy of the company to the reaction of investors. The population of this research is automotive and component companies which are listed in Indonesia Stock Exchange in 2010-2014, it has been retrieved by using purposive sampling and based on the determination criteria, and the samples are 8 companies with the 40 firm years which have met the criteria. The data analysis method has been done by using multiple regressions analysis.Based on the result of multiple regressions analysis, it shows that the financial performance and dividend share has an influence to the reaction of investors. Based on the result of R test, it shows that financial performance and dividend policy variables are feasible to explain the variable of the reaction of the investor reaction is 39.6%. Based on the result of F test with the significance level is 5%, so the result of the research shows that financial performance (return on investment (ROI), debt to equity ratio (DER), earning per share (EPS), and dividend policy (DPR) have influence to the reaction of the investor (abnormal return), so that it is feasible to use t test. The result of hypothesis test shows that return on investment (ROI) has positive influence to the reaction of the investor, debt to equity ratio (DER) has positive influence to the reaction of the investor, earning per share (EPS) has positive influence to the reaction of the investor, and dividend policy (DPR) has positive influence to the reaction of the investor.Keywords: financial performance, dividend policy, the reaction of investors.